Sequence diversity of kappa light chains from patients with AL amyloidosis and multiple myeloma - Schreiner, Sarah; Berghaus, Natalie; Poos, Alexandra; Raab, Marc-Steffen; Besemer, Britta; Fenk, Roland; Goldschmidt, Hartmut; Mai, Elias K.; Müller-Tidow, Carsten; Weinhold, Niels; Hegenbart, Ute; Huhn, Stefanie; et al. (Amyloid, 2024)
AL amyloidosis (AL) results from the misfolding of immunoglobulin light chains (IG LCs). Aim of this study was to comprehensively analyse kappa LC sequences from AL patients in comparison with multiple myeloma (MM). We analysed IGKV/IGKJ usage and associated organ tropism and IGKV1/D-33 in terms of mutational analysis and theoretical biochemical properties. cDNA and bulk RNA sequencing of the LCs of AL and MM patients. We studied 41 AL and 83 MM patients showing that IGKV1 was most expressed among kappa AL and MM, with higher frequency in AL (80% vs. 53%, p = .002). IGKV3 was underrepresented in AL (10% vs. 30%, p = .014). IGKJ2 was more commonly used in AL than in MM (39% vs. 29%). Patients with IGKV1/D-33 were associated with heart involvement (75%, p = .024). IGKV1/D-33-segments of AL had a higher mutation count (AL = 12.0 vs. MM = 10.0). FR3 and CDR3 were most frequently mutated in both, with a median mutation count in FR3 being the highest (AL = 4.0; MM = 3.5) and one mutation hotspot (FR3 (83I)) for IGKV1/D-33/IGKJ2 was associated with cardiac involvement. This study confirmed that germline usage has an influence on AL amyloidosis risk and organ involvement.
Gesehen am 04.04.2024